STRUCTURE, POWERS AND CHARACTERISTICS OF THE ACTIVITIES OF THE EUROPEAN PARLIAMENT - Вархов, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the features of the internal structure of the European Parliament as a legislative body of the European Union. The attention is focused on its powers and characteristics of its activities in the institutional system of the European Union. The article provides an analysis of influence of the political groups’ activities on the policy of both the European Union and the international arena. Peculiarities of the treaty mechanism of integration into the European Union are reflected in the characteristic features of its institutional framework. Together the bodies form an integrated system in which each institution of the European Community has significant importance both individually and in a legal connection with others. Considering the fact that Ukraine’s national interests are directly linked to the integration into the European Union, one of the instruments for the implementation of this task is to study the institutional mechanism of the Community and to apply some operation principles in practice. There is also a particularly important tendency to increase the influence of decisions of one of the main EU institutions, namely the European Parliament, on the situation in Ukraine. It is necessary to take into account the fact that the European Parliament, as the legislative body of the European Union, ratified Association Agreement on September 16, 2014, and therefore the relationship between Ukraine and the EU has moved to a new format based on the principles of political association and economic integration. Apart from the aforementioned points, it is important that as a result of EU enlargement, Ukraine borders directly with it which contributes to closer cooperation with the EU and the member states. Therefore, a study of the institutional mechanism of the European Union, in particular of legal status, party structure, powers of the European Parliament and participation in decision-making, is an actual problem for the further study. In the past 20 years the European Parliament has evolved from a consultative body to the full member of the legislative process in the European Union and is currently one of the key authorities in Europe, along with such institutions as the European Commission and the EU Council. Since the founding of the European Parliament, its position in the system of governing bodies of the European Union has undergone significant consolidation. The Lisbon Treaty continued the tradition of other constituent treaties of the European Communities to install only the basic principles of election. With it coming into force in 2009, the powers of the legislative body expanded to the powers of the Council of Ministers of the European Union. Most decisions in foreign policy require today the participation of the European Parliament. During the research, the author identified that nowadays the European Parliament plays an important role in the European Union and fulfils the following powers: legislative, budgetary, control and foreign policy. In the European Parliament there are the following groups of political parties that are organized based on their ideological commonality: the European People’s Party, the Progressive Alliance of Socialists and Democrats, the Alliance of Liberals and Democrats for Europe, the Greens – European Free Alliance, the European Conservatives and Reformists, the European United Left / Nordic Green Left, the Europe of Freedom and Democracy. It is determined that the legislative body of the European Union is formed by the centre-right politicians uniting Christian democratic, conservative parties; social democrats which include all the leading socialist, social democratic and labour national European parties; liberals that represent liberal parties and centrist direction; left-wing politicians who combine extreme left socialist and communist parties; green and regionalist parties combining national parties of ecologists and regionalists; Eurosceptic and far-right parties which include European nationalist parties and the parties of anti-European orientation.